La política de vivienda social en México desde la perspectiva funcional gubernamental (The policy of social housing in México from the government functional perspective) - Leal Iga, Jorge (Facultad de Contaduría Pública y Administración U.A.N.L., 2012)
Abstract. This research shows how in a passive or dynamic way do the housing policies had been set in México with different purposes than giving dignified housing to the citizens and on different sections of historic times since the Mexican Revolution has the government in turn been trying to use them as a control valve over the population and even as a politic or economic benefit. Based on the methodology used in this study it´s detected four moments in México´s social housing policy that have a common factor in a consistent way when the "Howard Jacob Karger & David Stoesz" social policy analysis model is used.